Dissociation of H+2 in intense femtosecond laser fields studied by coincidence three-dimensional momentum imaging - Wang, P. Q.; Sayler, A. M.; Carnes, K. D.; Xia, J. F.; Smith, M. A.; Esry, B. D.; Ben-Itzhak, I. (My University, 2006)
The dissociation of H+2 in an intense laser field has been experimentally studied using femtosecond laser pulses at 790nm in the intensity range of 1013–1015W/cm2. Kinematically complete measurements of both the ionic H+ and neutral H fragments dissociated from a vibrationally excited H+2 beam have been achieved by a coincidence three-dimensional momentum imaging system. Angular-resolved kinetic energy release spectra for a series of different intensity ranges have been obtained using the intensity-difference spectrum method, thus disentangling the problem caused by the intensity volume effect. Our results indicate that the dissociation dynamics are drastically different for “long” (135fs) and “short” (45fs) laser pulses at similar high laser intensities. Specifically, bond softening is found to be the main feature in long pulses, while above threshold dissociation is dominant in short pulses whose durations are comparable with the vibrational period of the molecule. Bond softening in short pulses appears at low kinetic energy release with a narrow angular distribution. The experimental results are well interpreted by solving the time-dependent Schrödinger equation in the Born-Oppenheimer representation without nuclear rotation.